Blockade and antiblockade effects with near-ground state neutral atoms - Attie, Jorge Antonio Gonçalves (2022)
In this work we study the photon blockade and antiblockade effects in a system of neutral atoms with a two-level structure, in the limit where induced dipole-dipole interactions mediated by light are relevant. Such system is an interesting alternative to cold gases platforms with Rydberg atoms, with applications in quantum optics and quantum information protocols. For an ensemble of few atoms driven by a laser field, we monitor the photon statistics and the population dynamics of the excited states, identifying the regime of parameters under which blockade or antiblockade is achieved. Furthermore we study the correlations, non-classicality and entanglement of the emitted photons through the photon-photon correlations function and the Cauchy-Schwarz and Bell’s inequalities, with the aim of obtaining a source of pairs of photons strongly correlated and entangled.